Atrophy and structural variability of the upper cervical cord in early multiple sclerosis. (June 2015) - Biberacher, Viola; Boucard, Christine C; Schmidt, Paul; Engl, Christina; Buck, Dorothea; Berthele, Achim; Hoshi, Muna-Miriam; Zimmer, Claus; Hemmer, Bernhard; Mühlau, Mark
Background: Despite agreement about spinal cord atrophy in progressive forms of multiple sclerosis (MS), data on clinically isolated syndrome (CIS) and relapsing–remitting MS (RRMS) are conflicting. Objective: To determine the onset of spinal cord atrophy in the disease course of MS. Methods: Structural brain magnetic resonance imaging (MRI) was acquired from 267 patients with CIS (85) or RRMS (182) and 64 healthy controls (HCs). The upper cervical cord cross-sectional area (UCCA) was determined at the level of C2/C3 by a segmentation tool and adjusted for focal MS lesions. The coefficient of variation (CV) was calculated from all measurements between C2/C3 and 13 mm above as a measure of structural variability. Results: Compared to HCs (76.1±6.9 mm 2 ), UCCA was significantly reduced in CIS patients (73.5±5.8 mm 2, p =0.018) and RRMS patients (72.4±7.0 mm 2, p <0.001). Structural variability was higher in patients than in HCs, particularly but not exclusively in case of focal lesions (mean CV HCs/patients without/with lesions: 2.13%/2.55%/3.32%, all p -values<0.007). UCCA and CV correlated with Expanded Disability Status Scale (EDSS) scores ( r =−0.131/0.192, p =0.044/<0.001) and disease duration ( r =−0.134/0.300, p =0.039/< 0.001). CV additionally correlated with hand and arm function ( r =0.180, p =0.014). Conclusion: In MS, cervical cord atrophy already occurs in CIS. In early stages, structural variability may be a more meaningful marker of spinal cord pathology than atrophy.